ITALIAN VALIDATION OF THE SOCIOPOLITICAL CONTROL SCALE FOR YOUTH (SPCS‐Y). Issue 4 (May 2014) - Vieno, Alessio; Lenzi, Michela; Canale, Natale; Santinello, Massimo
<x xml:space="preserve">Abstract</x> The aim of the study is to validate the two‐dimensional structure of the Sociopolitical Control Scale for Youth (SPCS‐Y) in a sample of Italian adolescents and to investigate associations of this interpersonal component of psychological empowerment with different measures of psychosocial adjustment. The questionnaires were filled out by a sample of 1, 376 (57.6% females; mean age = 17.24, standard deviation = .99) 11th‐ to 13th‐grade students. The two‐dimensional structure of the SPCS‐Y provided a significantly better fit to the data than the one‐factor model in the sample. Furthermore, students high in both leadership competence and policy control were found to be higher in perceived school importance, neighborhood attachment, and community and school participation. The results are consistent with previous studies from other countries and indicate that the SPCS‐Y is a valid instrument to assess sociopolitical control among Italian adolescents and possibly among those from other Mediterranean countries.